Content Validity Results Of Students' Perceptions of Children With Autism Spectrum Disorders - Widia Maharani; Rahmahtrisilvia Rahmahtrisilvia; Mega Iswari; Rila Muspita (Universitas Muhammadiyah Enrekang, 2024)
This research is intended to see the results of the research instrument that has been tested for validity to provide valid intersection data. Therefore, the validity of the contents of the research instrument should be tested before use. CVI, performed with a quantitative descriptive approach, is one of the methods that can be used to test the validity of content. The results showed that the validation of the lift consisting of two elements of content and language had an i-CVI average of 0.87 and the s -CVI was 0.87. The lift was considered appropriate, relevant, and valid based on those values. Regarding the validity of the trigger, the results showed that 13 issues had a high validity criterion with i-CVI 0.67, 29 issues had very high validation criteria with i -CVI more than 1,00, and the s - CVI value was 0.87.